Exploring factors hindering SMEs' growth: evidence from Nambia. Issue 2 (4th July 2016) - Baporikar, Neeta; Nambira, Geoffrey; Gomxos, Geroldine
Abstract : Purpose: This study aims to explore factors hindering small and medium-sized enterprises' (SMEs) growth in Khomas region in Nambia. Methodology/design/approach: Methodology adopted is qualitative approach with a case study research design including in-depth interviews and deep observations. Findings: Findings indicate that these SMEs experience stealing, security problems and fights from the customers, which hinder business growth. In addition, though they understand the importance of technology in boosting business growth, they are not able to keep the pace with changing technology, which impacts their business development. It was further found that access to finance, appropriate marketing strategies, lack of skilled manpower and poor customer service also hinder their business growth. Research limitations/implications: The special aspect of case study design is that it defines the delimitation of the research study and may find it necessary to adjust the boundaries that in any case have initially been determined arbitrarily. Being a case approach, it may be difficult to generalize for all kinds of SMEs. Practical implications: The problem faced by business owners as explored in this study brings a further dimension to the current literature on factors that hinder growth of SMEs. According to literature studies on factors hindering business growth, especially for SMEs selling alcoholic beverages, factors such as fighting, stealing and insulting as found in this study provide a new dimension on popular businesses especially in high-density areas or locations as they are popularly known in Namibia. Originality/value: The originality of this study is the line of business - SMEs selling alcoholic beverages. This line of business is very popular and many venture into this because of the demand and profitability but because there are no studies, this paper will contribute and provide a framework to ensure success and business growth for future entrepreneurs in this line of business.